Botanical Extracts Used as Wine Preservatives - Charalampos Proestos; Konstantinos Sflomos; Panagiotis Zoumpoulakis; Panagiotis Tatarides; Vassilia J Sinanoglou (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2015)
The aim of the study was to eliminate the potentially harmful sulfite salts normally added to wine - based products for preservation purposes with the introduction into the wine natural products, with pronounced antioxidant activity. Frieze - dried samples taken from the plants Hippophaes and Goji Berry were added to dry white and red wines after their fermentation phase. In all sample tests the sensory and oenological characteristics remained almost unchanged compared to original samples (without the addition of natural products), although their antioxidant activity was significantly increased when leaves of the plant Hippophaes were added. Goji berry fruits and fruit of Hippophaes plant increased antioxidant activity compared to original samples.